DAMPAK KENAIKAN PRODUKTIVITAS INDUSTRI PERTANIAN TERHADAP KINERJA EKONOMI SEKTORAL, EKONOMI MAKRO DAN PENDAPATAN RUMAH TANGGA - Haryono, Dwi; Tambunan, Mangara; Oktaviani, Rina; Siregar, Hermanto (Indonesian Journal of Socio Economics)
This research examines impacts of agricultural industry productivity improvement on sectoral and macro economic performance and household income. The CGE-AGRINDO model combined with CGE ORANI-F, INDOF, WAYANG, and ORANIGRD were used as a main tool of analysis. The data was computed using GEMPACK program. The study used data of I-O 2003. The are three simulations being examined, i.e. (1) improvement of agro industrial productivity, (2) simulation 1 plus improvement of agricultural productivity, and (3) simulation 2 plus improvement of financial institution. The policy simulations show that the impact of productivity improvement of agricultural industry tends to increase industry output and employment, but decrease the output price. The simulation also suggestt that productivity on agroindustry increases the macro economic performance and household income.